1997
DOI: 10.1210/mend.11.13.0029
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Wild Type and Dominant-Negative p55PIK Regulatory Subunit of Phosphatidylinositol 3-Kinase with Insulin-Like Growth Factor-1 Signaling Proteins

Abstract: In a first series of experiments done in the yeastPIK interacts with key elements in the IGF-I signaling pathway, and that these interactions are negatively modulated by PI 3-kinase itself, providing circuitry for regulatory feedback

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…This phenomenon suggests that p55γ may mediate insulin signaling mainly via association with IR rather than IRS‐1. In addition, a recent study demonstrated a tight association between insulin‐like growth factor receptor and p55γ [24], also suggesting a crucial role for p55γ as an adapter protein for insulin or the IGF receptor, rather than IRS‐1 protein.…”
Section: Resultsmentioning
confidence: 97%
“…This phenomenon suggests that p55γ may mediate insulin signaling mainly via association with IR rather than IRS‐1. In addition, a recent study demonstrated a tight association between insulin‐like growth factor receptor and p55γ [24], also suggesting a crucial role for p55γ as an adapter protein for insulin or the IGF receptor, rather than IRS‐1 protein.…”
Section: Resultsmentioning
confidence: 97%
“…The effects of wortmannin on insulin-stimulated glucose transport can be overcome by addition of membrane-permeable forms of PIP $ [46], providing further evidence that PI 3-kinase is involved. Specific evidence for the involvement of class 1a PI 3-kinases in this process was provided by studies with dominant negative forms of the p85 and p55 PIK adapter\regulatory subunits which block insulin stimulation of glucose transport and glucose-transporter translocation [39,266,267]. This has since been bolstered by the finding that constitutively active forms of p110 are able to induce GLUT4 translocation to the plasma membrane in a range of cell types, albeit to a lesser extent than insulin [43,268,269].…”
Section: Vesicle Traffic and Glucose-transporter Translocationmentioning
confidence: 99%
“…Mutation of class III PI 3-kinase, which produces only PI(3)P, impairs vesicular morphology and the endocytic pathway (1,19). Studies using a dominant-negative form of class I PI 3-kinase have implicated PI(3,4)P 2 and/or PI(3,4,5)P 3 in DNA synthesis (20), membrane ruffling (21), and glucose metabolism (22)(23)(24)(25).…”
mentioning
confidence: 99%